2017
DOI: 10.1007/s00213-017-4597-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cognitive training in substance use disorder: the effect of working memory training on impulse control in methamphetamine users

Abstract: ObjectivesImpulsivity is a vulnerability trait for poor self-regulation in substance use disorder (SUD). Working memory (WM) training improves impulsivity and self-regulation in psychiatric disorders. Here we test WM training in methamphetamine use disorder (MUD).MethodsThere are 15 MUD patients receiving inpatient treatment as usual (TAU) and 20 who additionally completed WM cognitive training (CT) and 25 healthy controls (HC). MANCOVA repeated measures analyses examined changes in impulsivity and self-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 50 publications
2
79
0
7
Order By: Relevance
“…These researches have already indicated the underlining relationship between cognitive training and impulsive control enhancement, either measure by cognitive tasks or self-report measures [32,34]. In this study,our results not only revealed the similar trend, but also in cognitive tasks such as DDT and IGT.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These researches have already indicated the underlining relationship between cognitive training and impulsive control enhancement, either measure by cognitive tasks or self-report measures [32,34]. In this study,our results not only revealed the similar trend, but also in cognitive tasks such as DDT and IGT.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have proved that computerized cognitive related training showed promising treatment effect and even brain plasticity in substance use disorder patients, such as stimulants, cocaine, methamphetamine, alcohol and nicotine [32,33]. However, these researches either only used cognitive training such as working memory training or cognitive bias modification training.…”
Section: Discussionmentioning
confidence: 99%
“…This includes targeting underlying processes involved in impulsivity and SUDs (i.e., working memory (WM) and attention) to validate behavioral measures of impulsivity . For instance, WM training can improve SUD outcomes . The second approach, behavioral measures are easy to administer in both species, thus requiring a modest amount of training, which may allow the ability to determine the efficacy of individualized treatments targeting impulsivity and SUD .…”
Section: Trait Factors In Impulsivity As Targets For Sud Treatment Dementioning
confidence: 99%
“…Three studies have been conducted investigating behavioral treatments for impulsivity and stimulant use. Black and Rosen conducted an RCT of the Advisor‐Teller monetary manager (ATM) intervention compared with a control condition in cocaine users. ATM addresses money management problems in substance abuse and provides help from therapists with planning and monitoring budgets .…”
Section: Treatment Of Co‐occurring Impulsivity and Sudsmentioning
confidence: 99%
See 1 more Smart Citation